Pengaruh literasi dan pengalaman keuangan terhadap penggunaan kartu kredit pekerja di Banyuwangi - Cintya Restu Destianata (Journal of Business & Banking, 2016)
Nowadays, credit card is not any longer a luxury good because it is not only owned the rich. In addition, to use it wisely, the users should have adequate financial literacy and financial experience. This study aims to examine the impact of financial literacy and financial experience on credit card usage by the workers. The data were collected using a questionnaire. The respondents were taken from 110 workers in Banyuwangi who have got credit cards with them. They were selected based using snowball sampling. The data were analyzed by using Multiple Regression Analysis, this study finds that financial experience positively affects the credit card usage, but financial literacy has no effect on it.